A ternary positive electrode material applied to a halide solid-state battery and a preparation method and application thereof
Patent Information
- Application Number
- CN202611101862.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-27
AI Technical Summary
首先,Ni≥90%的超高镍正极材料在充放电过程中存在严重的各向异性体积变化,约6~8%,易导致正极颗粒开裂,与卤化物电解质的固-固界面接触恶化
[0025]本发明提供的应用于卤化物固态电池的三元正极材料,使用高镍核心保证了正极材料的高容量;使用过渡元素掺杂与锂元素掺杂、单晶化形貌等策略,确保了循环性能的提升;采用低温构建复合包覆层,阻止电解质分解而导致的阻抗剧增,提升正极材料的长循环稳定性能。
Smart Images

Figure CN122992024A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ternary cathode material technology, specifically relating to a ternary cathode material for halide solid-state batteries, its preparation method, and its application. Background Technology
[0002] With the increasing demand for high energy density, high safety, and long cycle life in lithium batteries from new energy vehicles, large-scale energy storage, and portable electronic devices, traditional liquid electrolytes, due to their susceptibility to leakage, poor thermal stability, and susceptibility to lithium dendrite short circuits, are no longer sufficient to meet the requirements of next-generation lithium batteries. All-solid-state lithium batteries are considered the core technological approach to solving these problems, and solid-state electrolytes are the key materials determining their performance.
[0003] Halogen solid electrolytes, such as Li3InCl6, Li3YCl6, and Li2ZrCl6, have advantages such as high ionic conductivity of 1.42~2.04 mS / cm, wide electrochemical window of 1.8~4.2 V, and good high-voltage stability. They are suitable for high-nickel cathode materials and have become the preferred electrolyte system for solid-state batteries.
[0004] Ultra-high nickel ternary cathode materials with Ni ≥ 90% possess advantages such as high specific capacity and high energy density, but they still face significant challenges when matched with halide electrolytes. Firstly, ultra-high nickel cathode materials with Ni ≥ 90% exhibit severe anisotropic volume changes (approximately 6-8%) during charge-discharge processes, easily leading to cathode particle cracking and deterioration of the solid-solid interface contact with the halide electrolyte. Secondly, the high residual lithium content on the surface of high-nickel cathode materials makes them prone to side reactions with halide electrolytes, generating a high-resistivity interface layer. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a ternary cathode material for halide solid-state batteries, its preparation method, and its application. This material is compatible with halide solid-state electrolytes and utilizes LiNi... (0.86~0.91) Co (0.03~0.07) Mn (0.04~0.005) M 1 a M 2 b The triple structure design of O2 core-gradient cobalt shell-lithium-ion conductor coating and bifunctional bulk phase doping achieves interfacial chemical stability, bulk structure enhancement and rapid lithium-ion transport, solving problems such as severe interfacial side reactions, structural collapse and frequent cracking in existing technologies, and meeting the requirements of high energy density and long cycle life of all-solid-state batteries.
[0006] The technical solution adopted in this invention is as follows:
[0007] This invention provides a ternary cathode material for use in halide solid-state batteries, wherein the general chemical formula of the ternary cathode material is: LiNi (0.86~0.91) Co (0.03~0.07) Mn (0.04~0.005) M 1 a M 2 b O2@Li m X n Y p M 1 Selected from one or more of Zr, Y, Ti, W, Mo, and Sb; M 2 Selected from one or more of Mg, Al, Sr, B, and F; wherein a+b satisfies 0.005 ≤ a+b ≤ 0.02; Li m X n Y p It is one of LiNbO3, Li3PO4, Li2ZrO3, and Li3InCl6; the Li m X n Y p As a coating layer.
[0008] This invention also provides a method for preparing a ternary cathode material for halide solid-state batteries, the method comprising the following steps:
[0009] (1) Ni 0.92 Co 0.03 Mn 0.05 The (OH)2 precursor, lithium source, bulk dopant one, and bulk dopant two are mixed uniformly and sintered at 750-850 °C under an oxygen atmosphere. After cooling, the mixture is pulverized and sieved to obtain a sintered material. The bulk dopant one is any one or more of ZrO2, Y2O3, TiO2, H2WO4, MoO3, and Sb2O5; the bulk dopant two is any one or more of MgO, Al2O3, SrCO3, LiF, and H3BO3.
[0010] (2) Mix the first sintering material with the cobalt source evenly, and sinter at 550~650 °C in an oxygen atmosphere. After cooling, crush and sieve to obtain the second sintering material.
[0011] (3) Disperse the two materials in a solvent to obtain a suspension, add a coating agent to the suspension, disperse ultrasonically, remove the solvent at 80~120 °C, sinter at 200~400 °C under a protective atmosphere, cool and then crush and sieve to obtain a ternary cathode material for halide solid-state batteries; the coating agent is any one or more of NH4H2PO4, LiNbO3, InCl3 and LiCl, and ZrOCl·8H2O.
[0012] In step (1), Ni 0.92 Co 0.03 Mn 0.05 Assuming a total molar amount of Ni, Co, and Mn in the (OH)2 precursor is 100 mol, the amount of lithium source added is 105 ~ 108 mol; in bulk dopant one and bulk dopant two, the molar amount of a single dopant element added is 0.04 ~ 1.0 mol, and the total molar amount of all dopant elements added is 0.5 ~ 2.0 mol.
[0013] In step (1), the lithium source is one or both of lithium hydroxide and lithium carbonate; the sintering time is 10-15 h; and the heating rate to the sintering temperature is 2-5 °C / min.
[0014] In step (2), the cobalt source is cobalt hydroxide; with Ni 0.92 Co 0.03 Mn 0.05 The total molar amount of Ni, Co, and Mn in the (OH)2 precursor is 100 mol, and the amount of lithium source added is 2~5 mol; the sintering time is 8~12 h; and the heating rate to the sintering temperature is 2~5 °C / min.
[0015] In step (3), the coating agent is any one or more of the following: NH4H2PO4, LiNbO3, ZrOCl·8H2O, InCl3 and LiCl;
[0016] In step (3), when the coating agent is NH4H2PO4, LiNbO3, or ZrOCl·8H2O, the protective atmosphere is oxygen; when the coating agent is a mixture of InCl3 and LiCl, the protective atmosphere is nitrogen or argon.
[0017] In step (3), the solvent is a mixture of ethanol and deionized water; the solid content of the suspension is 10~20 wt%; and the concentration of the coating agent in the suspension is 0.1~0.5 mol / L.
[0018] In step (3), the sintering time is 2 to 5 hours.
[0019] The present invention also provides the application of the ternary cathode material in halide solid-state batteries.
[0020] The present invention also provides a halide solid-state battery, wherein the positive electrode active material of the halide solid-state battery is the ternary positive electrode material described in the present invention, which has excellent energy storage and cycle performance.
[0021] Existing technologies often involve randomly mixing multiple metal oxides for doping, making it difficult to simultaneously achieve lattice stability and lithium-ion conductivity. This invention screens doping elements based on ion valence state, bonding characteristics, and lattice occupancy behavior, classifying them into two categories. The first category includes high-valence metal elements such as Zr, Y, Ti, W, Mo, and Sb. These elements, upon entering the transition metal layer, can form stronger metal-oxygen covalent bonds, suppressing lattice oxygen precipitation during charging and discharging, mitigating lattice distortion caused by the H2-H3 phase transition, and preventing the formation of irreversible rock salt phases. This primarily addresses the issues of structural collapse and rapid cycle decay in high-nickel materials. The second category includes Mg, Al, Sr, B, and F. These ions can partially occupy the lithium layer, forming a "pillar effect," widening lithium-ion diffusion channels, and improving the material's rate performance. F⁻ can replace lattice oxygen, reducing the residual lithium content on the material surface and minimizing side reactions. Introducing a combination of these two types of doping elements into the matrix achieves a dual synergistic modification of framework strengthening and ion conductivity optimization, compensating for the performance limitations of single-type doping.
[0022] Conventional high-nickel ternary materials employ either a uniform Co ratio across the entire surface or a low-Co design on the surface, which has two major drawbacks: firstly, the low-cost Ni on the surface... 2+ High content, Ni easily undergoes irreversible phase transition at high potentials, and at the same time... 2+ It is easily leached and reacts with solid halide electrolytes to form a high-impedance insulating impurity phase; secondly, abrupt changes in core-shell composition can cause lattice mismatch, leading to interfacial stress concentration during charge-discharge volume deformation, which in turn causes surface cracking and peeling of the particles. This invention constructs a Co gradient structure with a linear increase from the core to the surface, where the molar proportion of Co in the core is fixed at 3%, and the Co content in the surface is increased to 5-6%. 3+ Without the Jahn-Teller distortion effect, a high proportion of Co enriched in the surface layer can effectively suppress the transformation from layered facies to rock salt facies and reduce the surface reactive Ni. 2+ The reduced content significantly alleviates Ni dissolution and improves chemical compatibility with halide solid electrolytes. The core maintains a low Co and high Ni ratio to maximize the material's high reversible capacity advantage, while the high Co content on the surface stabilizes the interface and suppresses phase transitions. The gradient transition structure achieves a balance between capacity and cycling stability, overcoming the inherent defects of uniform or abrupt core-shell structures.
[0023] Traditional Co surface coating modification is insufficient to suppress the continuous evolution of trace amounts of oxygen on the surface during charging and discharging. This oxygen directly contacts the Li3InCl6 halide solid electrolyte, causing Cl... -Diffusion towards the positive electrode side leads to displacement reactions with transition metals and oxygen, generating high-resistivity byproducts such as In-O and Ni-Cl, continuously increasing the interfacial impedance. Therefore, an additional dense lithium-ion conductor coating layer needs to be constructed outside the Co gradient matrix. This invention selectively selects four types of lithium-ion conductors—LiNbO3, Li3PO4, Li2ZrO3, and Li3InCl6—as coating materials, unlike traditional inert insulating oxides such as Al2O3 and TiO2: these four coating phases possess lithium-ion conductivity themselves and do not hinder Li... + Intercalation / deintercalation; electrochemical stability window covers the 2.1–3.6 V operating range, no decomposition at high potentials; bidirectional blocking of Cl. - Inward diffusion and outward dissolution of transition metal ions block the pathways for interfacial side reactions; both can be prepared using low-temperature processes, without damaging the single-crystal matrix and the internal Co gradient distribution structure. Different coating materials have differentiated advantages: Li3PO4 is chemically inert and inexpensive, and can passivate residual lithium on the surface; LiNbO3 has high lattice matching and excellent ionic conductivity, providing long-term barrier properties against Cl. - Li2ZrO3 and the Zr doping of the substrate synergistically enhance the lattice's oxygen-locking ability, making it suitable for high-temperature operating conditions; Li3InCl6 is homogeneous with the solid electrolyte, eliminating the heterogeneous interface barrier, making it suitable for high-rate scenarios. By compositing this type of ultrathin coating film on the outer Co gradient layer, a three-layer protection system is formed: "bulk phase dual-doped stable lattice - near-surface high Co gradient anti-phase transition - outer lithium conductor coating to isolate the interface," which solves the three core pain points of high-nickel halide solid batteries from the inside out: structure, phase transition, and interface corrosion.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The ternary cathode material for halide solid-state batteries provided by this invention uses a high-nickel core to ensure high capacity; employs strategies such as transition element doping and lithium doping, and single-crystal morphology to ensure improved cycle performance; and uses low-temperature construction of a composite coating layer to prevent the surge in impedance caused by electrolyte decomposition, thereby improving the long-term cycle stability of the cathode material.
[0026] The present invention provides a simple and low-cost method for preparing ternary cathode materials for halide solid-state batteries. A first-calcination step involves doping with a bifunctional bulk phase to suppress lattice distortion and improve rate performance; a second-calcination step suppresses the irreversible phase transition of the layered structure to the rock salt phase and reduces the surface Ni content. 2+ The generation of Li reduces + / Ni 2+ Mixed arrangement; finally, a low-temperature coating step is performed, taking into account Li + This method facilitates the conduction and suppression of side reactions at the electrode / electrolyte interface. It is fully compatible with existing ultra-high nickel ternary cathode material production processes and can be scaled up for large-scale production. Attached Figure Description
[0027] Figure 1 SEM image of the ternary cathode material prepared in Example 1;
[0028] Figure 2 This is a SEM image of the ternary cathode material prepared in Example 2. Detailed Implementation
[0029] The present invention will now be described in detail with reference to the embodiments.
[0030] Unless otherwise specified, all raw materials used in the embodiments and comparative examples can be purchased directly.
[0031] Example 1
[0032] A ternary cathode material for use in halide solid-state batteries, with the general chemical formula LiNi. 0.877 Co 0.062 Mn 0.04 9Zr 0.006 Mg 0.009 O2@Li3PO4.
[0033] The preparation method of the ternary cathode material includes the following steps:
[0034] (1) Ni 0.92 Co 0.03 Mn 0.05 10 kg of (OH)2 precursor, 4.2 kg of LiOH·H2O, 80 g of ZrO2 (1 mol%), and 40 g of MgO (0.5 mol%) were mixed and stirred at 1500 rpm for 40 min. Under an oxygen atmosphere, the mixture was heated to 800°C at a heating rate of 3°C / min and sintered for 12 h. After cooling, the mixture was pulverized and sieved through a 300-mesh sieve to obtain a sintered material.
[0035] (2) Mix 10 kg of the first calcined material with 0.35 kg of Co(OH)2, stir at 1200 rpm for 50 min, and sinter at 600 °C for 10 h under an oxygen atmosphere at a heating rate of 4 °C / min. After cooling, crush the material and sieve it through a 350 mesh sieve to obtain the second calcined material.
[0036] (3) 10 kg of the calcined material was dispersed in 100 L of a mixed solvent of ethanol and water with a volume ratio of 1:1. Ammonium dihydrogen phosphate was added to make the concentration 0.3 mol / L. The mixture was ultrasonically dispersed for 30 min, stirred in a water bath at 100 °C for 3 h, the solvent was evaporated, and the mixture was sintered at 350 °C for 4 h under an oxygen atmosphere. After cooling, the mixture was pulverized and sieved through a 350-mesh sieve to obtain LiNi, a ternary cathode material for halide solid-state batteries.0.877 Co 0.062 Mn 0.049 Zr 0.006 Mg 0.009 O2@Li3PO4. Its SEM image is shown below. Figure 1 As shown in the figure, it can be seen that it has a typical single crystal morphology.
[0037] Example 2
[0038] A ternary cathode material for use in halide solid-state batteries, with the general chemical formula LiNi. 0.869 Co 0.068 Mn 0.04 7Y 0.009 Al 0.009 O2@LiNbO3.
[0039] The preparation method of the ternary cathode material includes the following steps:
[0040] (1) Ni 0.92 Co 0.03 Mn 0.05 10 kg of (OH)2 precursor, 4.2 kg of LiOH·H2O, 110 g of Y2O3 (0.8 mol%), and 50 g of Al2O3 (0.7 mol%) were mixed and stirred at 1000~2000 rpm for 30~60 min. Under an oxygen atmosphere, the mixture was heated to 820 °C at a heating rate of 3 °C / min and sintered for 12 h. After cooling, the mixture was pulverized and sieved through a 350 mesh sieve to obtain a calcined material.
[0041] (2) Mix 10 kg of the first calcined material with 0.42 kg of cobalt hydroxide, stir at 1200 rpm for 50 min, and sinter at 600 °C for 10 h under an oxygen atmosphere at a heating rate of 4 °C / min. After cooling, crush the material and sieve it through a 350 mesh sieve to obtain the second calcined material.
[0042] (3) 10 kg of the sintered material was dispersed in 100 L of a mixed solvent of ethanol and water with a volume ratio of 1:1. Lithium niobate was added to make the concentration 0.3 mol / L. The mixture was ultrasonically dispersed for 30 min, stirred in a water bath at 90 °C for 2 h, the solvent was evaporated, and the mixture was sintered at 350 °C for 4 h under an oxygen atmosphere. After cooling, the mixture was pulverized and sieved through a 350 mesh sieve to obtain LiNi, a ternary cathode material for halide solid-state batteries. 0.869 Co 0.068 Mn 0.047 Y 0.009 Al 0.009 O2@LiNbO3. Its SEM image is as follows. Figure 1As shown in the figure, it can be seen that it has a typical single crystal morphology.
[0043] Example 3
[0044] A ternary cathode material for use in halide solid-state batteries, with the general chemical formula LiNi. 0.886 Co 0.056 Mn 0.04 8Ti 0.007 Sr 0.004 O2@Li3InCl6.
[0045] The preparation method of the ternary cathode material includes the following steps:
[0046] (1) Ni 0.92 Co 0.03 Mn 0.05 10 kg of (OH)2 precursor, 4.1 kg of LiOH·H2O, 60 g of TiO2 (0.9 mol%), and 70 g of SrCO3 (0.6 mol%) were mixed and stirred at 1500 rpm for 40 min. Under an oxygen atmosphere, the mixture was heated to 795 °C at a heating rate of 3 °C / min and sintered for 12 h. After cooling, the mixture was pulverized and sieved through a 350-mesh sieve to obtain a sintered material.
[0047] (2) Mix 10 kg of the first calcined material with 0.28 kg of cobalt hydroxide, stir at 1200 rpm for 50 min, and sinter at 600 °C for 8 h under an oxygen atmosphere at a heating rate of 3 °C / min. After cooling, crush the material and sieve it through a 350 mesh sieve to obtain the second calcined material.
[0048] (3) 10 kg of the calcined material was dispersed in 100 L of a mixed solvent of ethanol and water with a volume ratio of 1:1. Li3InCl6 was added to make the concentration 0.4 mol / L. The mixture was ultrasonically dispersed for 30 min, and then dried under vacuum stirring at 80 °C to remove the solvent. The mixture was sintered at 350 °C for 3 h under a nitrogen atmosphere. After cooling, the mixture was pulverized and sieved through a 350-mesh sieve to obtain LiNi, a ternary cathode material for halide solid-state batteries. 0.886 Co 0.056 Mn 0.048 Ti 0.007 Sr 0.004 O2@Li3InCl6.
[0049] Example 4
[0050] A ternary cathode material for use in halide solid-state batteries, with the general chemical formula LiNi. 0.871 Co 0.065 Mn 0.04 7Zr 0.004Y 0.005 Mg 0.007 O2@Li2ZrO3.
[0051] The preparation method of the ternary cathode material includes the following steps:
[0052] (1) Ni 0.92 Co 0.03 Mn 0.05 10 kg of (OH)2 precursor, 4.25 kg of LiOH·H2O (6.5 mol% lithium excess), 50 g of ZrO2 (0.6 mol%), 60 g of Y2O3 (0.5 mol%), and 30 g of MgO (0.4 mol%) were mixed and stirred at 1500 rpm for 40 min. Under an oxygen atmosphere, the mixture was heated to 800 °C at a heating rate of 3 °C / min and sintered for 12 h. After cooling, the mixture was pulverized and sieved through a 350-mesh sieve to obtain a sintered material.
[0053] (2) Mix 10 kg of the first calcined material with 0.28 kg of cobalt hydroxide, stir at 1200 rpm for 50 min, and sinter at 600 °C for 8 h under an oxygen atmosphere at a heating rate of 3 °C / min. After cooling, crush the material and sieve it through a 350 mesh sieve to obtain the second calcined material.
[0054] (3) 10 kg of the calcined material was dispersed in 100 L of a mixed solvent of ethanol and water with a volume ratio of 1:1. Zirconium oxychloride was added to make the concentration 0.3 mol / L. The mixture was ultrasonically dispersed for 30 min, stirred at 90°C for 3 h, evaporated to dryness, sintered at 380°C for 4 h under an oxygen atmosphere, cooled, pulverized, and sieved through a 350-mesh sieve to obtain LiNi, a ternary cathode material for halide solid-state batteries. 0.871 Co 0.065 Mn 0.047 Zr 0.004 Y 0.005 Mg 0.007 O2@Li2ZrO3.
[0055] Comparative Example 1:
[0056] Directly using commercially available single-crystal NCM90 (LiNi) 0.9 Co 0.05 Mn 0.05 O2), no bulk doping, no Co gradient shell, no coating layer.
[0057] Comparative Example 2
[0058] A method for preparing a ternary cathode material for halide solid-state batteries, which is the same as in Example 1 except that the sintering time in step (2) is changed to 3h and the concentration of ammonium dihydrogen phosphate in step (3) is changed to 0.6 mol / L.
[0059] Application examples
[0060] Application of ternary cathode materials prepared in various embodiments and comparative examples in halide solid-state batteries
[0061] All-solid-state molded battery assembly:
[0062] The solid electrolyte Li3InCl6 was spread flat in a 10 mm polyether ether ketone (PEEK) sleeve and pressed into a sheet with a force of 300 MPa to obtain a solid electrolyte sheet.
[0063] Then, the cathode materials prepared in each embodiment and comparative example, solid electrolyte Li3InCl6, and VGCF were mixed uniformly at a mass ratio of 70:29:1 to form a composite cathode, which was then uniformly spread on one side of the solid electrolyte sheet and pressed under a pressure of 300 MPa for 5 min.
[0064] Indium foil, lithium foil, and copper foil are placed sequentially on the other side of the solid electrolyte sheet, and the positive and negative ends are fixed with stainless steel stamps. The pressure is maintained at 100 MPa for 1 min.
[0065] Electrochemical testing:
[0066] Each battery model was placed in a stainless steel frame to maintain a pressure of 100 MPa, while simultaneously being tested in a 30 °C oven. The test voltage range was 2.1–3.6 V. The first three charge-discharge cycles were performed at 0.1C, 0.2C, and 0.2C, respectively, followed by 50 charge-discharge cycles at a 0.5C rate. The electrical performance results are shown in Table 1.
[0067] Table 1
[0068]
[0069] As can be seen from Table 1, the batteries prepared with the cathode materials prepared in Examples 1-4 have a first charge specific capacity ≥231 mAh / g, a first discharge specific capacity ≥205 mAh / g, a first coulombic efficiency ≥87%, and a 50-cycle retention rate ≥85%.
[0070] The battery prepared using the cathode material in Comparative Example 1 exhibits a first-charge specific capacity of only 208.4 mAh / g, a first-discharge specific capacity of only 174.1 mAh / g, an initial coulombic efficiency of only 83.5%, and a 50-cycle retention rate of only 66.1%. This demonstrates the superior performance of LiNi... 0.9 Co0.05 Mn 0.05 Bulk doping with O2 to construct a Co gradient structure from the core to the surface, followed by an additional dense lithium-ion conductor coating layer on the outside of the Co gradient matrix, can significantly improve the performance of LiNi. 0.9 Co 0.05 Mn 0.05 Performance of O2 ternary cathode material.
[0071] The battery prepared using the cathode material in Comparative Example 2 exhibited a first-charge specific capacity of only 215.2 mAh / g, a first-discharge specific capacity of only 179.6 mAh / g, a first-cycle coulombic efficiency of only 83.5%, and a 50-cycle retention rate of only 68.1%. This demonstrates that even with increased concentrations of the subsequent coating layer raw materials, the performance of the prepared ternary cathode material is inferior to that of the examples if the second calcination time is too short. This is because the Co in the coating layer does not diffuse sufficiently towards the core, with only a portion reacting with Li. + The cobalt bonds into the crystal lattice, with the remaining portion remaining as a low-valent cobalt oxide (Co3O4, CoO) impurity phase. This impurity phase is electrochemically inert and has poor conductivity, reducing the proportion of effective active material. Secondly, the intrinsic stabilizing effect of the cobalt-rich layer fails, making it unable to effectively reduce Li... + / Ni 2+ The degree of mixing increases the resistance to lithium-ion diffusion and raises polarization; at the same time, the highly active Ni on the surface... 2+ It is more easily dissolved and undergoes interfacial side reactions with Li3InCl6 halide solid electrolyte, continuously generating high-resistivity impurity phases, resulting in a decrease in the 50-cycle retention rate.
[0072] The above-described detailed description of a ternary cathode material for halide solid-state batteries, its preparation method, and its application is illustrative rather than limiting. Several embodiments may be listed within the defined scope. Therefore, variations and modifications that do not depart from the overall concept of the present invention should be within the protection scope of the present invention.
Claims
1. A ternary cathode material for use in halide solid-state batteries, characterized in that, The general chemical formula of the ternary cathode material is: LiNi (0.86~0.91) Co (0.03~0.07) Mn (0.04~0.005) M 1 a M 2 b O2@Li m X n Y p M 1 Selected from one or more of Zr, Y, Ti, W, Mo, and Sb; M 2 Selected from one or more of Mg, Al, Sr, B, and F; wherein a+b satisfies 0.005 ≤ a+b ≤ 0.02; Li m X n Y p It is one of LiNbO3, Li3PO4, Li2ZrO3, and Li3InCl6; the Li m X n Y p As a coating layer.
2. A method for preparing a ternary cathode material for halide solid-state batteries, characterized in that, The preparation method includes the following steps: (1) Ni 0.92 Co 0.03 Mn 0.05 The (OH)2 precursor, lithium source, bulk dopant one, and bulk dopant two are mixed uniformly and sintered at 750-850 °C under an oxygen atmosphere. After cooling, the mixture is pulverized and sieved to obtain a sintered material. The bulk dopant one is any one or more of ZrO2, Y2O3, TiO2, H2WO4, MoO3, and Sb2O5; the bulk dopant two is any one or more of MgO, Al2O3, SrCO3, LiF, and H3BO3. (2) Mix the first sintering material with the cobalt source evenly, and sinter at 550~650 °C in an oxygen atmosphere. After cooling, crush and sieve to obtain the second sintering material. (3) Disperse the two materials in a solvent to obtain a suspension, add a coating agent to the suspension, disperse ultrasonically, remove the solvent at 80~120 °C, sinter at 200~400 °C under a protective atmosphere, cool and then crush and sieve to obtain a ternary cathode material for halide solid-state batteries; the coating agent is any one or more of NH4H2PO4, LiNbO3, InCl3 and LiCl, and ZrOCl·8H2O.
3. The preparation method according to claim 2, characterized in that, In step (1), Ni 0.92 Co 0.03 Mn 0.05 Assuming a total molar amount of Ni, Co, and Mn in the (OH)2 precursor is 100 mol, the amount of lithium source added is 105 ~ 108 mol; in bulk dopant one and bulk dopant two, the molar amount of a single dopant element added is 0.04 ~ 1.0 mol, and the total molar amount of all dopant elements added is 0.5 ~ 2.0 mol.
4. The preparation method according to claim 2 or 3, characterized in that, In step (1), the lithium source is one or both of lithium hydroxide and lithium carbonate; the sintering time is 10-15 h; and the heating rate to the sintering temperature is 2-5°C / min.
5. The preparation method according to claim 2 or 3, characterized in that, In step (2), the cobalt source is cobalt hydroxide; with Ni 0.92 Co 0.03 Mn 0.05 The total molar amount of Ni, Co, and Mn in the (OH)2 precursor is 100 mol, and the amount of lithium source added is 2~5 mol; the sintering time is 8~12 h; and the heating rate to the sintering temperature is 2~5 °C / min.
6. The preparation method according to claim 2 or 3, characterized in that, In step (3), the coating agent is any one or more of the following: NH4H2PO4, LiNbO3, ZrOCl·8H2O, InCl3 and LiCl; when the coating agent is NH4H2PO4, LiNbO3, or ZrOCl·8H2O, the protective atmosphere is oxygen; when the coating agent is a mixture of InCl3 and LiCl, the protective atmosphere is nitrogen or argon.
7. The preparation method according to claim 2 or 3, characterized in that, In step (3), the solvent is a mixture of ethanol and deionized water; the solid content of the suspension is 10~20 wt%; and the concentration of the coating agent in the suspension is 0.1~0.5 mol / L.
8. The preparation method according to claim 1, characterized in that, In step (3), the sintering time is 2 to 5 hours.
9. The application of the ternary cathode material as described in claim 1 in halide solid-state batteries.
10. A halide solid-state battery, characterized in that, The positive electrode active material of the halide solid-state battery is the ternary positive electrode material as described in claim 1.
